Androcles and the lion - Simmons, Jean, 1929-2010; Mature, Victor; Young, Alan; Shaw, Bernard, 1856-1950; Erskine, Chester, 1905-1986 (Classic collection., 1987)
Androcles, a tailor in Imperial Rome, volunteers to be the first Christian to face a hungry lion in the Coliseum because he once took a thorn from the animal's paw.